Phenotypic and Genotypic Characteristics of SCN1A Associated Seizure Diseases - Chen, Chunhong; Fang, Fang; Wang, Xu; Lv, Junlan; Wang, Xiaohui; Jin, Hong (Frontiers in Molecular Neuroscience, 2022)
Although SCN1A variants result in a wide range of phenotypes, genotype-phenotype associations are not well established. We aimed to explore the phenotypic characteristics of SCN1A associated seizure diseases and establish genotype-phenotype correlations. We retrospectively analyzed clinical data and results of genetic testing in 41 patients carrying SCN1A variants. Patients were divided into two groups based on their clinical manifestations: the Dravet Syndrome (DS) and non-DS groups. In the DS group, the age of seizure onset was significantly earlier and ranged from three to 11 months, with a median age of six months, than in the non-DS group, where it ranged from seven months to two years, with a median age of 10 months. In DS group, onset of seizures in nine patients was febrile, in seven was afebrile, in two was febrile/afebrile and one patient developed fever post seizure. In the non-DS group, onset in all patients was febrile. While in the DS group, three patients had unilateral clonic seizures and the rest had generalized or secondary generalized seizures, in the non-DS group, all patients had generalized or secondary generalized seizures without unilateral clonic seizures. The duration of seizure in the DS group was significantly longer and ranged from 2 min to 70 min (median, 20 min), than in the non-DS group where it ranged from one min to 30 min (median 5 min). Thirty-one patients harbored de novo variants, and nine patients had inherited variants. Localization of missense variants in the voltage sensor region (S4) or pore-forming region (S5–S6) was seen in five of the nine patients in the DS group and nine of the 19 patients in the non-DS group. The phenotypes of SCN1A-related seizure disease were diverse and spread over a continuous spectrum from mild to severe. The phenotypes demonstrate commonalities and individualistic differences and are not solely determined by variant location or type.